2019
DOI: 10.36380/jwpr.2019.3
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Dietary Inclusion of Probiotics on Growth and Intestinal Morphology of Broiler Chickens

Abstract: Probiotics are currently under investing the most valuable substances alternative to antibiotic growth promoters in poultry breeding practice. This research was performed to evaluate the effect of supplementing broiler drinking water with probiotics (Pediococcus acidilactici and Bacillus subtilis) at a concentration of ≥10 8 CFU/ml during 42 days of feeding period on growth performance and gut health. A total of 144 one-day-old Ross 308 broiler chicks (mixed gender) with an average initial BW of 42.3 g were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
3
2
0
Order By: Relevance
“…The feed conversion ratios in feed intake per unit gain in weight for the birds from group T 3 were significantly higher than control, T 1 and T 2 groups (Table 2). The present study results agree with Williams et al (2022) and Youssef et al (2017) who reported significantly better FCR by addition of prebiotic and acidifier in diet, respectively. However, Kim et al (2011) and Heidari et al (2018) observed non-significant effect (p>0.05) on FCR in broiler birds supplemented with prebiotic and acidifier respectively in broiler diet.…”
Section: Growth Performancesupporting
confidence: 92%
See 2 more Smart Citations
“…The feed conversion ratios in feed intake per unit gain in weight for the birds from group T 3 were significantly higher than control, T 1 and T 2 groups (Table 2). The present study results agree with Williams et al (2022) and Youssef et al (2017) who reported significantly better FCR by addition of prebiotic and acidifier in diet, respectively. However, Kim et al (2011) and Heidari et al (2018) observed non-significant effect (p>0.05) on FCR in broiler birds supplemented with prebiotic and acidifier respectively in broiler diet.…”
Section: Growth Performancesupporting
confidence: 92%
“…The average feed consumption of birds of the experimental groups, T 3 group has higher comparable with C, T 1 and T 2 group. Present findings (Table 2) are in agreement to the findings of Saleh et al (2014) and Youssef et al (2017) who reported significant effect on feed consumption due to supplementation of prebiotic and acidifier powder respectively. However, contradicting the findings of the present study, Taherpour and Ghasemi (2014) reported non-significant (p>0.05) effect on feed intake due to fed of prebiotic with acidifier combination.…”
Section: Growth Performancesupporting
confidence: 92%
See 1 more Smart Citation
“…However, Youshelf et al (2017) reported that supplements of single lactic acid (0,2%) in broiler diets seem to obtain better performances than the organic acid mixture (0,4%). It was also found that the inclusion of single lactic acid in broiler diets declined the serum cholesterol level, the pH of small intestine, the counts of fecal coliforms and E. coli, but did not affect the carcass yield, breast, or organ weights [94].…”
Section: Effect Of Acidifiers On Poultry Productionmentioning
confidence: 97%
“…Probiotic preparations usually comprise of probiotic bacterial strains that are acid-tolerant bacteria producing lactic acid (an organic acid) after carbohydrate fermentation as a main metabolic end-product. The antimicrobial effects caused by organic acids have been well acknowledged [22][23][24]. The low pH will decrease the pathogenic bacteria while assisting the propagation of the probiotic and other advantageous, organic acid-tolerant microbes in the gastrointestinal tract [25].…”
Section: Introductionmentioning
confidence: 99%